Detection and genotyping of GBV-C/HGV variants in China - Lu, Ling; Ng, Mun Hon; Zhou, Bei-Ping; Luo, Hong-Tao; Nakano, Tatsunori; Robertson, Betty H.; Im, Stanley W.K. (Virus research, 2001)
We detected GBV-C/HGV sequences in the sera from 64 out of a total of 324 subjects in the south of China. In agreement with findings of others, we noted an especially high rate of infection among intravenous drug addicts and patients with chronic hepatitis C virus infection. The detection was achieved by nested PCR to amplify the 5′ noncoding region (5′NCR) of the viral genome. Sequence analysis of the resulting 234 bp product revealed a total of 26 different sequences of which 25 were found to belong to the genotype G3, which is the most prevalent genotypes among Asian isolates, and one belonged to genotype G1, common among African isolates. The sequence divergence between the genotypes was largely clustered in a short variable region (V2) within the 5′NCR, and we showed that genotyping may be achieved equally well by analysis of this variable region as by the more detail analysis of the entire 5′NCR or of the entire viral genome.